Deep Ocean Minerals Minimize Eccentric Exercise-Induced Inflammatory Response of Rat Skeletal Muscle - Saovieng, Suchada; Wu, Jinfu; Huang, Chih-Yang; Kao, Chung-Lan; Higgins, Matthew F.; Chuanchaiyakul, Rungchai; Kuo, Chia-Hua (Frontiers in Physiology, 2018)
Background: We have previously shown an accelerated recovery from muscle fatigue in men challenged by prolonged exercise after oral deep ocean minerals (DOM) supplementation. Here, we hypothesized a decrease in eccentric exercise-induced muscle inflammation in rats regularly consuming DOM-containing drinks (hardness 600 mg/L; fructose 11%). Methods: Forty-seven male Sprague Dawley rats were randomized into 4 groups: Control (C, N = 12), Fructose (F, N = 12), Fructose + Exercise (FE, N = 12), and Fructose + Exercise + DOM (FED, N = 11). Since fructose is a commonly used ingredient in beverages, 11% of fructose was added as a vehicle of the study. Soleus muscles of rats were analyzed 24 hours after an acute bout of downhill running following 9 weeks of DOM supplementation. Results: Leukocyte infiltration and TNF-α mRNA of muscle in the FE group were 5 times and 4 times greater the F group, respectively (P < 0.05). Both markers in the FED group were significantly lower than those in the FE group (P < 0.05). IL-10 mRNA of muscle in the F group was > 8 fold greater than the C group (P < 0.05). The reduced glutathione (GSH) of muscle in the F group was 34% lower than that in the C group (P < 0.05). However, GSH levels were similar for the C and FED groups. Conclusion: Prolonged fructose supplementation modulates inflammatory balance of rat skeletal muscle. The results of the study suggest that DOM can minimize eccentric exercise-induced inflammatory cytokine responses in rat skeletal muscle.